Convict criminology and the struggle for inclusion - Ross, Jeffrey Ian (Critical criminology, 2016)
Convict Criminology (CC) began in the early 1990s as a reaction to the then current state of academic criminology that did not adequately reflect the voices of convicted felons. Since its beginnings, CC has attempted to draw attention to a range of problems created by the criminal justice apparatus and defenders of the status quo. Dr. Joanne Belknap’s 2014 ASC presidential address and subsequent article presented an argument that stressed the importance of activism to be considered as part of criminological research. In the process, she reviewed her career and then criticized the field of Critical Criminology, in particular Convict Criminology. The article, however, ignored the numerous efforts that CC has engaged in to build an inclusive group school, movement, organization and network that includes the diverse voices of Ph.D. educated convicts and excons, and overall reflected a superficial understanding of the history and intent of Convict Criminology. This article attempts to explain the shortcomings of Belknap’s article and clarifies misunderstandings.